2005
DOI: 10.1016/j.jbankfin.2004.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous product differentiation in credit markets: What do borrowers pay for?

Abstract: This paper studies strategies pursued by banks in order to differentiate their services from those of their rivals. In that way the level of competition in the industry is reduced. More specifically we analyze whether the bank size, a bank's ability at avoiding losses, or its capital ratio can be used as strategic variables to make banks different and increase the interest rates banks can charge their borrowers in equilibrium. Using a panel of data covering Norwegian banks between 1993 and 1998 we find empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Consequently, more low-quality borrowers are able to obtain financing. Kim et al (2005) found that banks' ability to avoid loses may act as a strategic variable to make them different and increase their market power and interest rates. The high quality banks with lower loses signal their creditworthiness to other stakeholders (such as shareholders) and through better management of loans change dividends policies.…”
Section: Product Market Competitionmentioning
confidence: 99%
“…Consequently, more low-quality borrowers are able to obtain financing. Kim et al (2005) found that banks' ability to avoid loses may act as a strategic variable to make them different and increase their market power and interest rates. The high quality banks with lower loses signal their creditworthiness to other stakeholders (such as shareholders) and through better management of loans change dividends policies.…”
Section: Product Market Competitionmentioning
confidence: 99%
“…Second, we examine the disciplining role of borrowers in addition to the role of depositors. To the best of our knowledge, there is only one empirical study that shows the significance of the role played by borrowers in disciplining banks (Kim, Kristiansen, & Vale, 2005 demonstrated with Norwegian banks).…”
Section: Introductionmentioning
confidence: 99%
“…However, the impact of HHI varies widely across studies and its magnitude is often much lower (see e.g. Kim, Kristiansen and Vale, 2005;Degryse and Ongena, 2008).…”
Section: Concentration and Loan Ratesmentioning
confidence: 99%